Pendampingan Masyarakat Melalui Manajemen Fundrising dalam Upaya Menghimpun Dana dan Mempercepat Renovasi Pembangunan Masjid Baiturrahim Nganjuk - Arif Zunaidi; Fachrial Lailatul Maghfiroh (Jurnal Ilmiah Pangabdhi, 2022)
The mosque is a place of worship used by Muslims to practice worship and other activities related to religious activities. Of course, as a place of worship, it needs comfort to add solemnity to worship. From its establishment as the only mosque in the hamlet of Kaliulo in 1980 until now, it has not changed much. Coupled with the growing number of heads of families reaching 350 families, of course, a renovation is necessary for comfort in worship to increase. This community service is in the form of training and mentoring, i.e., providing training to provide an understanding of the fundraising management function to mobilize public funds as well as assisting the takmir of the mosque and the renovation committee for the construction of the Baiturrahim mosque through the management of fundraising. The purpose of this service is to provide training and an introduction to fundraising management to the community of Kaliulo Hamlet, as well as assistance to the Renovation Committee on how to obtain funds to finance the activities of renovation. The first activities were carried out, although some things were still missing. This success can be seen by the increase in the amount of funds and development materials obtained by the fundraising team and the success of the fundraising team in trying new things in order to speed up the process of renovation and construction of the Baiturrahim Mosque.